Application of a Mixture of Rabbit Fertilizer and Manure on Several Varieties of Chilli (Capsicum Frutescens L.) on Plant Growth And Yield - Wirajaya, Anak Agung Ngurah Mayun; Yuliartini, Made Sri; Udayana, I Gusti Bagus; Mahardika, Ida Bagus Komang; Aulia, Fadilla; Ryantobi, Anggeline Barek Oran (Formosa Journal of Applied Sciences, 2024)
This research aims to obtain the best mixture of rabbit fertilizer with manure and the response to the best chili varieties. This research is a factorial experiment, with a basic randomized block design (RAK) with 2 factors being tried. The first factor with 3 levels: K 0 = no manure, K 1 = rabbit manure + cow manure, K 2 = rabbit manure + chicken manure.  Second factor with 3 chili varieties: V1= Rawita, V2= Ori 212, V3= Caliber and repeated 3 times. K1 gave the highest value for the fresh weight of harvested fruit per plant, namely 250.63 g. The Caliber V3 variety gave the highest value for the fresh weight of harvested fruit per plant, namely 252.87 g.